2012
DOI: 10.1073/pnas.1200081109
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs miR-125a and miR-125b constitutively activate the NF-κB pathway by targeting the tumor necrosis factor alpha-induced protein 3 ( TNFAIP3, A20 )

Abstract: Constitutive activation of the NF-κB pathway is associated with diffuse large B-cell lymphoma (DLBCL) pathogenesis, but whether micro-RNA dysfunction can contribute to these events remains unclear. Starting from an integrative screening strategy, we uncovered that the negative NF-κB regulator TNFAIP3 is a direct target of miR-125a and miR-125b, which are commonly gained and/or overexpressed in DLBCL. Ectopic expression of these microRNAs in multiple cell models enhanced K63-linked ubiquitination of proximal si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
233
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(244 citation statements)
references
References 35 publications
6
233
1
2
Order By: Relevance
“…[95][96][97][98][99][100][101] Other oncomiRs include miR-125a and miR-125b, which aberrantly target TNFAIP3, leading to constitutive NF-kB activation. 102 On the contrary, several key miRNAs that target antiapoptotic genes are downregulated or deleted in lymphoid tumors. For example, miR-15a/16-1 acts as a tumor suppressor in CLL by targeting BCL2.…”
mentioning
confidence: 99%
“…[95][96][97][98][99][100][101] Other oncomiRs include miR-125a and miR-125b, which aberrantly target TNFAIP3, leading to constitutive NF-kB activation. 102 On the contrary, several key miRNAs that target antiapoptotic genes are downregulated or deleted in lymphoid tumors. For example, miR-15a/16-1 acts as a tumor suppressor in CLL by targeting BCL2.…”
mentioning
confidence: 99%
“…Within the recent two decades, more than 140 conserved miRNAs were discovered that have specific target site on 72 candidate genes for lupus and LN (18). The investigations could show that some miRNAs play a central role in the pathogenesis of LN by reducing production of pro-inflammatory mediators as well as with inhibiting lymphocyte function (19)(20)(21)(22)(23). In the present study, we assessed the expression of three introduced genes including miR638, miR-146a, miR-198 and miR-371 in LN patients.…”
Section: Discussionmentioning
confidence: 99%
“…MIR125B down-regulates the expression of IRF4 and PRDM1 (Malumbres et al, 2009), and recently MIR125A/B were shown to directly target TNFAIP3, a negative regulator of the NF-jB pathway. Overexpression of either of these miRNAs were found to increase the aggressiveness of DLBCL cell lines (Kim et al, 2012). Furthermore, a strong correlation between NF-jB activity and expression levels of MIR125A/B in primary DLBCL cases was reported.…”
Section: Mir125bmentioning
confidence: 91%